2020
DOI: 10.1080/13696998.2020.1751649
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of cardiac implantable electronic device infections: cost analysis at one year in a large U.S. health insurer

Abstract: Aims: Cardiac device infections (CDIs) are serious adverse events associated with morbidity and mortality, significant costs and increased healthcare utilization. The objective of the current study was to characterize the CDI rate by device type, risk factors for infection and healthcare costs from a large U.S. health insurer perspective. Materials and Methods: A retrospective analysis of a large U.S. health insurer database identified commercial and Medicare Advantage with Part D (MAPD) members !18 years with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“… 21 Infections are one of the most feared complications leading to substantial morbidity and 3-fold risk of mortality. 4 In spite of best practice, 1% to 4% of CIED procedures are associated with infection within 12 months, 6 , 22 25 and risk accumulates over the lifetime of the patient. 26 The impact of a CIED infection to the healthcare system is substantial, with each event costing $48 000 to $55 000 to treat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 Infections are one of the most feared complications leading to substantial morbidity and 3-fold risk of mortality. 4 In spite of best practice, 1% to 4% of CIED procedures are associated with infection within 12 months, 6 , 22 25 and risk accumulates over the lifetime of the patient. 26 The impact of a CIED infection to the healthcare system is substantial, with each event costing $48 000 to $55 000 to treat.…”
Section: Discussionmentioning
confidence: 99%
“… 26 The impact of a CIED infection to the healthcare system is substantial, with each event costing $48 000 to $55 000 to treat. 1 , 25 , 27 29 To date, only the TYRX absorbable antibacterial envelope has been shown to significantly reduce the risk of CIED infection with the addition of preoperative antibiotics. 6 In addition to the prior finding that the antibacterial envelope is clinically effective, this analysis suggests that the envelope is also cost-effective in the US healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…We assumed half of the combined rate reported in the REPLACE registry could be attributed to lead failure (0.5%) and half could be attributed to lead dislodgement (0.5%). We estimated the one-year probability of lead infection after initial implant (1.22%) and after device replacement (2.16%) with a retrospective data analysis based on administrative claims from a large US insurer [21]. The lifetime risk of lead infection after the first year of an initial or replacement implant was double the value of the one-year claims-based probability [22].…”
Section: Clinical Datamentioning
confidence: 99%
“…[5][6][7][8][9][10][11] The incidence of CIED infections is estimated between 1% and 4% of CIED recipients. [5][6][7][8][12][13][14] In part due to the rising prevalence of certain risk factors among CIED recipients, the rate of CIED infection is reported to be increasing in excess of the implantation rate. 15 An infection risk score was developed from the Prevention of Arrhythmia Device Infection Trial (PADIT), as shown in the Supplemental Materials found at https://doi.org/10.1016/j.jval.202 0.12.021.…”
Section: Introductionmentioning
confidence: 99%